Landscape and water level changes in the Kunfehértó region - Baics, Tamás (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
During the old times, many natural areas have changed; its original habitat degraded or disappeared. The reasons of these changes are possibly multiple but there is one sure fact: the speed of these changes increased in the last few decades, 2-3 centuries. This allows us to conclude that these changes are not natural but if they ever were, they were tremendously fastened by people’s presence and activity. This problem is global and occurs around Kunfehértó, too. The formerly virgin area has totally altered until today. At the beginning, only the lake was here, surrounded by grasslands and a few forest spots. Today we can find a swimming facility, planted forests, recreation areas that surround the lake that is decreased in size and regulated by people. This change was examined with a time series analyses, and searched the reason of the changes based on the water level data.
Keywords: landscape change; time series analyses; soil water; precipitation; water level decrease